2019
DOI: 10.1352/1944-7558-124.3.191
|View full text |Cite
|
Sign up to set email alerts
|

More Than IQ: Executive Function Explains Adaptive Behavior Above and Beyond Nonverbal IQ in Youth With Autism and Lower IQ

Abstract: Adaptive behavior is a critical metric for measuring outcomes in those with autism spectrum disorder (ASD). Executive function skills predict adaptive behavior in youth with ASD with average or higher IQ; however, no study has examined this relationship in ASD with lower IQ (IQ ≤ 75). The current study evaluated whether executive function predicted adaptive behavior in school-age youth with ASD with lower IQ, above and beyond nonverbal IQ. We examined adaptive behavior and executive function through informant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 32 publications
6
34
0
Order By: Relevance
“…This replicates earlier findings, where age and cognitive ability but not ASD symptom severity contributed to variability in adaptive functioning in a sample of 125 toddlers (Ray-Subramanian et al, 2011). Other prognostic predictors of adaptive functioning identified in previous studies include executive functioning (Bertollo & Yerys, 2019) and level of language (Stone et al, 1999).…”
Section: Introductionsupporting
confidence: 89%
“…This replicates earlier findings, where age and cognitive ability but not ASD symptom severity contributed to variability in adaptive functioning in a sample of 125 toddlers (Ray-Subramanian et al, 2011). Other prognostic predictors of adaptive functioning identified in previous studies include executive functioning (Bertollo & Yerys, 2019) and level of language (Stone et al, 1999).…”
Section: Introductionsupporting
confidence: 89%
“…In addition, the specific empathy impairment of ASC individuals may be influenced by other factors, such as intelligence (Bertollo and Yerys, 2019), cognitive control (Hughes, 2001; Bertollo and Yerys, 2019), action anticipation (Sinha et al, 2014; Krogh-Jespersen et al, 2018), and implicit learning (Lieberman, 2000; Foti et al, 2015), among others. Especially relevant may be the empathy impairment of ASC individuals at the state level due to the situational dependence of state empathy itself (Kennedy and Adolphs, 2012; Chen and Liu, 2016; Powell and Roberts, 2017).…”
Section: Prospects and Limitationsmentioning
confidence: 99%
“…For example, some studies have found that ASC individuals have varying degrees of impairment in intelligence (Spencer et al, 2007), cognitive control (Solomon et al, 2008), implicit learning (Vivanti and Rogers, 2014), and action anticipation (Ganglmayer et al, 2019). Meanwhile, the impairment of intelligence, cognitive control, implicit learning, and action anticipation in ASC individuals can provide some explanation for their impairment in social communication (Lieberman, 2000; Hughes, 2001; Sinha et al, 2014; Foti et al, 2015; Krogh-Jespersen et al, 2018; Bertollo and Yerys, 2019). However, because the reports on these variables in the study of ASC individuals' empathy impairment are incomplete and the measurement tools are inconsistent, we do not further analyse these variables in this research.…”
Section: Introductionmentioning
confidence: 99%
“…EFs are a complex set of cognitive abilities necessary for emotion regulation, deliberate reasoning, and self-regulation that are required to reach suitable levels of adaptive functioning, quality of life, and wealth, often more than IQ scores and socioeconomic status [ 9 , 10 , 11 , 12 ]. In fact, the presence of difficulties in EFs can be considered as a transdiagnostic indicator of atypical development [ 13 ].…”
Section: Introductionmentioning
confidence: 99%